ANALISIS PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Pada Pegawai Perum PERUMNAS Jakarta) - Arina Nurandini; Eisha Lataruva (JURNAL STUDI MANAJEMEN ORGANISASI, 2014)
This study aims to analyze the influence of organizational commitment on employeeperformance in Perumnas Jakarta. And to know which one variable affectspredominantly between 3 variables namely affective commitment, normative commitment,and continuance commitment to employee performance in Jakarta Perumnas.The study uses three independent variables, namely affective commitment, normativecommitment and continuance commitment, with the dependent variable is theperformance of employees. The data in this study were collected through a questionnairedistributed to 75 employees in Jakarta Perumnas.Based on the research that has been done shows that affective commitment variable has apositive and significant influence on employee performance, variable normativecommitment has a positive and significant impact on employee performance, andcontinuance commitment variable has a positive and significant influence on employeeperformance.Keywords: Affective Commitment, Normative Commitment, Continuance CommitmentEmployee Performance.